Access to medicines by child refugees in the East Midlands region of England: a cross-sectional study. Issue 12 (18th December 2014) - Alkahtani, S; Cherrill, J; Millward, C; Grayson, K; Hilliam, R; Sammons, H; Choonara, I
Abstract : Objectives: To explore access to primary healthcare and drug therapy by refugee children in the East Midlands region of England. Design: Interviews with refugees with children and a control group of British parents with children. Setting: East Midlands region of England. Participants: 50 refugees with children and a control group of 50 parents with children. Main outcome measures: Number of medicines used by children in the last month and the past 6 months. Health of parents and children. Registration with a general practitioner (GP). Results: All families in both groups were registered with a GP. There was no difference in the number of children in the two groups experiencing illnesses .In the last month, 30 refugee children received 60 medicines and 31 control children 63 medicines. In the past 6 months, 48 refugee children received 108 medicines and 43 control children 96 medicines. There was no difference between the two groups of children in relation to the likelihood of receiving any medicines in either the last month (P=0.839) or the past 6 months (p=0.81). Children in the refugee group were more likely to receive prescribed medicines for the last month (p=0.008) and the past 6 months (p<0.001). They were also less likely to receive over the counter (OTC) medicines in the past 6 months (p=0.009). Conclusions: The refugee children in this study in the East Midlands had access to primary healthcare, medicines and a family doctor. They were more likely to receive prescribed medicines and less likely to receive OTC medicines, especially paracetamol.